2018
DOI: 10.3892/etm.2018.6617
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of LAMP, CPA and IMSA methods for rapid detection of the AML1/ETO fusion gene in acute myeloid leukemia

Abstract: The objective of the present study was to determine whether the loop-mediated isothermal amplification (LAMP), cross-priming amplification (CPA), and/or isothermal multiple-self-matching-initiated amplification (IMSA) methods can provide rapid detection of the runt related transcription factor 1/runt related transcription factor 1 translocation partner 1 (AML1/ETO) fusion gene in acute myeloid leukemia (AML). According to the sequence of the AML1/ETO fusion gene available in GenBank and the principles of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The three isothermal amplification assays demonstrated high specificity and sensitivity when detecting heat-labile enterotoxin-producing E. coli in clinical samples [24,28]. Additionally, research by Yang, et al also confirmed that IMSA demonstrated higher sensitivity than LAMP or CPA assays [19]. However, compared with other pathogenic bacteria, ETEC is more serotyped and relatively complicated.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The three isothermal amplification assays demonstrated high specificity and sensitivity when detecting heat-labile enterotoxin-producing E. coli in clinical samples [24,28]. Additionally, research by Yang, et al also confirmed that IMSA demonstrated higher sensitivity than LAMP or CPA assays [19]. However, compared with other pathogenic bacteria, ETEC is more serotyped and relatively complicated.…”
Section: Discussionmentioning
confidence: 89%
“…The primers are able to specifically recognize distinct corresponding regions of the target DNA and can typically generate multiple self-matching structures (SMS) similar to a dumbbell, which single-stranded DNA amplicons generate from the hybrid primers. This technology does not require complex instruments and the detection of target DNA sequences can be completed within 1-2 hours using isothermal conditions, for which the method is potentially rapid and simple allowing practical diagnosis of a specific disease [18,19]. Cross-priming amplification (CPA) was invented by Fang et al which uses a mechanism similar to LAMP with 4-8 nucleotide primers complementary to the DNA template and using a detection procedure achieved using isothermal conditions within 1 h [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the IMSA primers were designed according to the conserved region of the PCV3 capsid gene, which was the usual detective marker of PCR-based methods (7,11). The primer design work was not as complicated as those of LAMP, because the IMSA primers consisted of seven basic primers specifically recognizing distinct regions of the target, which can be easily designed by using the software Primer Premier 5.0 (15). The results of colorimetric IMSA can be visually judged within 60 min, which was at least 60 min shorter than qPCR or PCR methods.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved region of the capsid gene was determined by alignment of PCV3 strains indexed in the GenBank (accession no: MF589105.1 , MF589107.1 , MF769811.1 , MF769807.1 , MF084994.1 , KX778720.1 , KX898030.1 , MG310152.1 , MF079254.1 , and MG250187.1 ). According to the principle of IMSA assay, capsid gene sequences of PCV3-US/MO2015 strain (accession no: KX778720.1 ) were input for IMSA primer design by using the software Primer Premier 5.0 ( 15 ). Among multiple sets of primers, the primers targeting to the conserved regions of the capsid gene were selected for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation